The Indonesian Education Units Use of Digital Archives for Records Management - Nasution, Satri Dwi Kurnia; Natas, Ahmad Muchlisin Natas (Jurnal Manajemen Pendidikan, 2024)
Background The use of digital archives offers a great opportunity for educational institutions to improve efficiency, transparency and security of important data. Purpose This research aims to examine the role and benefits of digital archives implementation in Indonesian educational institutions, as well as the challenges faced in the digitisation process. Design/method/approach This research is a literature review, which discusses the importance of digital archives through various reference sources, namely Sciencedirect, Emerlad Insight and google schoolar. Results This research provides results on how archive digitisation can improve the management of academic and administrative data, accelerate access to information, and support better decision-making in educational environments. However, challenges such as lack of training, uneven technology infrastructure, and data security issues remain key barriers to the implementation of digital archives. The Indonesian government has initiated various programmes to accelerate this transition, including an integrated digital archive platform and training for educators and administrative staff. Contribution/value This research provides insights into the importance of digital archives in improving the efficiency of education administration and overcoming the challenges of the digital era.